Hermenêutica constitucional, meio ambiente e linguagem - Bruno Malta Pinto (2014)
The present study is based on the necessity of a more concrete approach of the component elements of the work of Hermeneutics, applied in a juridical ambit, after the linguistic turn. The incursions made about Philosophical Hermeneutics of gadamer matrix and also about the language, considering the ordinary language philosophy, when put in a scenarium of changes, felt in a post-modern society, give opportunity to new readings of a text and, also, open room for new readers. This research, based on these presumptions, is directed to the expression significant enviromental degradation, referred to in article 225, paragraph one, item IV, in the Brazilian Federal Constitution of 1988. The open texture of some of the Constitution`s dispositives, like the one that is the object of this investigation, allows for the concretion of these work elements, by withdrawing the Constitution of its dogmatic ostracism and transporting it to the reality, based on the contexts of those expressions, which permit an open comprehension of its meanings, and, by doing so, permit also a participative inclusion in the process of interpretation. The possibile extension of the range of interpreters of the Constitution oxygenates the law environment with new visions and comprehensions, giving an important role to the non-juridical interpreter in the task of implementing the Constitution`s mandaments. The dialogue and also the fusion of horizons from other interpreters, who have in the language their condition of possibility, offer new outlines to the Constitutional Hermeneutics. The reality lived by this researcher, given his vinculation to the Minas Gerais` Environmental and Susteinable Development Department, and the debates and experiences lived with the Environmental Policy Council of this federative unit, led to the choice of this work`s theme.